AKTIVITAS PEMECAHAN MASALAH SISWA DALAM MENGERJAKAN SOAL PISA DITINJAU BERDASARKAN TAHAPAN POLYA - Khairunnisa Khairunnisa; Ramlah Ramlah (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2021)
This study aims to describe students problem solving abilities in solving PISA based math problems in terms of Polya stages. This type of research is a descriptive study with a qualitative approach. Data collection techniques in this study used a mathematical problem solving ability test. The data analysis in this study is inductive because the results of the research emphasize the meaning rather than generalization. The research subjects consisted of 3 students of class XII SMK, namely 1 high ability student, 1 medium ability student, and 1 low ability student. The results showed that: (1) High ability students were able to solve math problems based on PISA by going through all stages of Polya. (2) Students with intermediate skills in solving PISA based math problems have not been able to go through all stages of Polya. They are only able to go through the stages of understanding the problem and making a plan. (3) Students with low abilities in solving math problems based on PISA have not been able to go through all stages of Polya. They are only able to go through the stage of understanding the problem.